Fingerprint Recognition System - Nur Aina , Zainal (UTeM, 2009)
Fingerprints are part of human identity. Fingerprints are the most mature biometric; automated method of recognition a person based on physical or behavioral characteristics technology. In this thesis, a neural network in MATLAB was used to train and simulated data of fingerprint. A multi-layer neural network based on the popular feed-forward (FF) algorithm has been used for classification. At the end, all the simulate network will interface with Graphical User Interface for user application.